Balloon‐occluded retrograde transvenous obliteration for recurrent fundal gastric variceal bleeding in an adolescent. (12th June 2014) - Rosen, Danya; Chu, Jaime; Patel, Rahul; Moon, Jang; Iyer, Kishore; Arnon, Ronen
Abstract Gastric variceal bleeding is associated with high morbidity and mortality. Balloon‐occluded retrograde transvenous obliteration is a relatively new treatment used to control bleeding gastric varices that involves transvenous sclerosis of gastric varices through a spontaneous gastrorenal shunt. Here, we report on a 14‐yr‐old patient that underwent balloon‐occluded retrograde transvenous obliteration for refractory bleeding fundal varices in the setting of esophageal varices and cirrhosis, which did not respond to medical management or endoscopic injection. This case report serves as a reminder that balloon‐occluded retrograde transvenous obliteration can successfully control fundal variceal bleeding in pediatric patients and may serve as a bridge to liver transplantation.